Myopathy associated with pigmentary degeneration of the retina and high protein content of cerebrospinal fluid - José Antonio Levy; Milberto Scaff; Ana Maria C. Tsanaclis; Vanderlei Garcia Rodrigues; Edgard Silva Lusvarghi (Arquivos de Neuro-Psiquiatria)
The cases of two brothers suffering from a myopathy associated with pigmentary degeneration of the retina and increase of protein content of the cerebrospinal fluid are reported.